Menanamkan Nilai-Nilai Perdamaian Dalam Mewujudkan Negara Ideal - Zaimah Official (TERAJU: Jurnal Syariah dan Hukum, 2021)
Violence in Indonesia are growing very fastly, not only between individuals with individuals, but also between groups to the century. Example bombing Oikumene church in Samarinda. The problems caused system of peace in cauntry can’t be well realized. So, in society and state must be applyed principle and the value of peace. The value of peace is love, tolerance, control, and leave violence. While the principle is honesty and responsibility (al-Amanah), justice (al-‘Adalah), brotherhood (al-Ukhuwah), respecting pluralism (al-Ta’addudiyah), equality (al-Musawah), consciousness (al-Syura), prioritizing peace (al-Silm) and control (Amr bi al-Ma’ruf Nahy ‘an Munkar). If applyed the value and principles in the state, so that have realized of peace and ideal cauntry.